Xsibox (Extended Side Table With Storage) / Muhammad Zubair Othman - Othman, Muhammad Zubair (2019)
The purpose of the study is to design a user-friendly side table that can reduce space usage in small house. This study also aims to evaluate the user's perception on the satisfaction of the side table design, material and function provided. The questionnaire analysed after had been distributed to 128 correspondents and target for those who had income either work in government or private sector. Based on the study made, it can conclude that XSiBox fulfil the opinion of the respondent. Mostly of the respondent accepted the idea of function of the XSiBox which have multipurpose features to minimize space. The respondent also agreed to the idea of the user-friendly applied on the side table. The respondent gave positive perception on the satisfaction of the side table design, material and function provided.